A CsPbX3 perovskite quantum dot / polymer composite luminescent material, its preparation method and application

CN122941408APending Publication Date: 2026-10-20LANZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611151952.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,钙钛矿量子点的软离子键性质和低的晶格能,导致其对热、紫外线和极性溶剂极其敏感,稳定性较差,限制了其实际应用和商业化进程

Benefits of technology

1、本发明通过原位光聚合的方式在CsPbX3钙钛矿量子点表面原位生长出聚合物壳层,实现了单粒子尺度的均匀包覆,制备方法简便高效;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a CsPbX3 perovskite quantum dot / polymer composite luminescent material, its preparation method, and its applications, belonging to the field of fluorescent materials technology. Using CsPbX3 quantum dot surface ligands as initiators, this invention grows a PMMA shell in situ on the surface of CsPbX3 quantum dots via in-situ photopolymerization, preparing a CsPbX3 / PMMA composite luminescent material coating individual quantum dots. This composite luminescent material exhibits excellent luminescent performance and superior water stability compared to CsPbX3 quantum dots; after immersion in water for 68 days, its luminescence intensity still retains 75% of its initial intensity. Furthermore, the material has uniform size and small particle size, making it promising for applications in Micro-LED devices and precision patterning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fluorescent material preparation technology, specifically relating to a CsPbX3 perovskite quantum dot / polymer composite luminescent material, its preparation method and application. Background Technology

[0002] CsPbX3 (X = Cl, Br, I) perovskite quantum dots (QDs) have shown promising applications in light-emitting diodes (LEDs) and solar cells due to their narrow full width at half maximum (FWHM), high photoluminescence quantum yield, and tunable emission spectra. However, the soft ionic bonding and low lattice energy of QDs make them extremely sensitive to heat, ultraviolet radiation, and polar solvents, resulting in poor stability and limiting their practical applications and commercialization. In recent years, researchers have developed various stability-enhancing strategies, with coating strategies showing particularly significant improvements. However, the formation of composite materials often sacrifices the dispersibility and compatibility of QDs, resulting in typically large particle sizes with poor compatibility with polar solvents. This makes microscale patterning via inkjet printing and other methods difficult, hindering the application of QDs in system-level integration platforms. Therefore, improving the long-term structural stability of QDs in polar solutions without sacrificing their dispersibility and compatibility is crucial. To achieve this, precise structural modification of individual QDs is necessary to achieve coating at the individual QD scale.

[0003] In recent years, researchers have explored surface modification of CsPbBr3 quantum dots at the single-particle level and achieved a series of results, including Al2O3 coatings grown by atomic layer deposition, SiO2 coatings obtained through one-pot synthesis, and CsPb2Br5 coatings obtained through a freeze-thaw restriction strategy. These methods can effectively coat CsPbBr3 quantum dots. Compared to oxides and metal halides, polymer molecules exhibit switchable conformational changes from dissolved coils to collapsing spheres in different solvents, demonstrating good dispersibility in suitable solvents. Combining polymers with CsPbBr3 quantum dots can provide strong support for high-resolution patterning processing. Therefore, finding a simple and effective method to coat CsPbX3 quantum dots with polymers at the single-particle scale to improve the colloidal stability of quantum dots is of great significance. Summary of the Invention

[0004] Based on the above, the purpose of this invention is to provide a simple and effective method for preparing CsPbX3 perovskite quantum dot / polymer composite luminescent materials.

[0005] Another object of the present invention is to provide a CsPbX3 perovskite quantum dot / polymer composite luminescent material prepared by the above method.

[0006] Another object of the present invention is to provide the application of the above-mentioned CsPbX3 perovskite quantum dot / polymer composite luminescent material in Micro-LEDs.

[0007] To achieve its purpose, the present invention adopts the following technical solution: This invention introduces a short-chain ligand—2-halopropionic acid—on the surface of CsPbX3 quantum dots, initiating atom transfer radical polymerization to generate a PMMA shell in situ on the quantum dot surface, resulting in a core-shell structured CsPbX3 / PMMA composite material, achieving encapsulation at the scale of a single CsPbX3 quantum dot. The prepared CsPbX3 / PMMA composite material exhibits excellent optical properties and good water stability, and the sample meets the requirements of Micro-LED for particle size and luminescent performance of the luminescent material. Compared to physically mixing PMMA and CsPbX3, the core-shell structured CsPbX3 / PMMA prepared by photopolymerization in this invention, based on its more effective interface construction and defect passivation effect, allows MMA monomers to polymerize around the CsPbX3 quantum dots during the in-situ polymerization process, resulting in a tighter and more continuous contact between the generated PMMA segments and the quantum dot surface, thus constructing a more complete polymer protective layer. Simultaneously, the carbonyl C=O in the PMMA molecule can react with uncoordinated Pb on the CsPbX3 surface. 2+ Coordination occurs, surface defects are passivated, and the nonradiative recombination process induced by trapped states is reduced, thus improving luminescence intensity and fluorescence quantum efficiency. In contrast, in physically mixed systems, PMMA is mostly mixed with CsPbX3 in the form of macromolecular chains, resulting in insufficient interfacial contact and difficulty in forming a uniform and dense coating layer. This limits the passivation effect on surface defects. Therefore, CsPbX3 / PMMA core-shell composites generally outperform simple physically mixed samples in terms of luminescence efficiency, resistance to damp heat, light stability, and storage stability.

[0008] The specific technical solution of this invention is as follows: A first aspect of the present invention provides a method for preparing a CsPbX3 perovskite quantum dot / polymer composite luminescent material, the method comprising the following steps: (1) CsX, PbX2, organic ligands, and N,N-dimethylformamide are mixed and stirred until completely dissolved to obtain a precursor solution; the molar ratio of CsX, PbX2, and organic ligands is 1:2:20; the precursor solution is injected into a benzene solvent with a stirring speed of 400-700 r / min and reacted at room temperature to obtain a CsPbX3 quantum dot solution; wherein, X represents halogens Cl, Br, and I; (2) Add the same volume of settling agent to the CsPbX3 quantum dot solution in step (1) and centrifuge to purify it, so as to obtain a CsPbX3 quantum dot colloidal solution; (3) The CsPbX3 quantum dot colloidal solution described in step (2) is subjected to photopolymerization reaction with the benzene solvent, tetrahydrofuran, and methyl methacrylate under a nitrogen atmosphere and under sealed stirring conditions to obtain the perovskite quantum dot / polymer composite luminescent material.

[0009] Preferably, in step (1), the organic ligand is any one or a mixture of oleylamine, 2-halopropionic acid, 2-halobutyric acid or 2-haloisobutyric acid.

[0010] Preferably, in steps (1)-(3), the benzene solvent is any one of toluene, xylene or ethylbenzene.

[0011] Preferably, in step (2), the settling agent is one or more of ethyl acetate, methyl acetate, or acetone. The centrifugal purification process is as follows: centrifuge at 12000 r / min for 5 min, redissolve the precipitate after centrifugation with a benzene solvent, and continue centrifuging at 7000 r / min for 3 min.

[0012] Preferably, in step (3), the volume ratio of benzene solvent, tetrahydrofuran, and methyl methacrylate is 0.2-0.7: 1.5-2.0: 0.5-0.7. The photopolymerization reaction conditions are: stirring speed of 500-700 r / min, ultraviolet light intensity of 12 W, distance of 10 cm, and photopolymerization time of 1-8 h.

[0013] A second aspect of the present invention provides a CsPbX3 perovskite quantum dot / polymer composite luminescent material prepared by the above method. The composite luminescent material is a core-shell structured nanomaterial obtained by in-situ growth of a polymer shell on the surface of CsPbX3 quantum dots, with the core being a CsPbX3 quantum dot embedded within the polymer. The excitation wavelength of the composite luminescent material is 250-500 nm, the emission wavelength is 400-700 nm, and the full width at half maximum (FWHM) of the emission spectrum is 12-42 nm. The particle size of the composite luminescent material is 10-400 nm.

[0014] A second aspect of the present invention provides the application of the above-mentioned CsPbX3 perovskite quantum dot / polymer composite luminescent material in Micro-LED devices and precision patterning.

[0015] By adopting the above technical solution, the beneficial effects of the present invention are as follows: 1. This invention grows a polymer shell on the surface of CsPbX3 perovskite quantum dots in situ through in-situ photopolymerization, achieving uniform coating at the single-particle scale. The preparation method is simple and efficient. 2. The CsPbX3 perovskite quantum dot / polymer composite luminescent material described in this invention has uniform size and small particle size, which meets the requirements of Micro-LED for the particle size of luminescent materials and can be used in Micro-LED devices; 3. The CsPbX3 perovskite quantum dot / polymer composite luminescent material of the present invention has the characteristics of high luminescence intensity, narrow emission spectrum half-peak width, and short fluorescence lifetime. It has the advantages of wide color gamut and high resolution in display device applications. 4. The stability of the CsPbX3 perovskite composite luminescent material described in this invention is superior to that of pure CsPbX3 quantum dots, and it has a wider range of application prospects compared to CsPbX3 quantum dots. Attached Figure Description

[0016] Figure 1 It is the chemical reaction equation for atom transfer radical polymerization initiated by CsPbBr3 quantum dot surface ligands; Figure 2 The X-ray diffraction (XRD) pattern and Fourier transform infrared (FTIR) spectrum of CsPbBr3 quantum dots and CsPbBr3 / PMMA obtained in Example 2 are shown. Figure 2 (a) X-ray diffraction patterns of CsPbBr3 quantum dots and CsPbBr3 / PMMA; Figure 2 (b) FTIR spectra of CsPbBr3 quantum dots and CsPbBr3 / PMMA; Figure 3 Transmission electron microscope (TEM) images of CsPbBr3 quantum dots and CsPbBr3 / PMMA obtained in Example 2; Figure 3 a is a TEM image of CsPbBr3 quantum dots prepared using 2-bromopropionic acid / oleylamine (2-BPA / OAm) as ligands; Figure 3 b is an HRTEM image of CsPbBr3 quantum dots; Figure 3 c is a TEM image of CsPbBr3 / PMMA; Figure 3 d is the HRTEM image of CsPbBr3 / PMMA; Figure 4 The emission spectra and fluorescence decay curves of CsPbBr3 quantum dots and CsPbBr3 / PMMA obtained in Example 2 are shown. Figure 4 a represents the absorption and emission spectra of CsPbBr3 quantum dots and CsPbBr3 / PMMA; Figure 4 b represents the fluorescence decay curves of CsPbBr3 quantum dots and CsPbBr3 / PMMA; Figure 5The curves showing the change in luminescence intensity of CsPbBr3 quantum dots and CsPbBr3 / PMMA obtained in Example 2 as a function of immersion time in water, and photographs of CsPbBr3 / PMMA samples immersed in water. Figure 6 It is the CsPbBr3 / PMMA composite material obtained in Example 2 combined with a 460 nm blue light chip and K2SiF6:Mn 4+ Spectral images, light emission photographs, and color gamut diagrams of white LED devices fabricated with red phosphors; Figure 6 a represents the CIE coordinates and color gamut of the white LED fabricated from the composite material. Figure 6 b represents the electroluminescence spectrum of the white LED device; Figure 7 For (a)Y3Al5O 12 Photograph of a display device obtained by welding commercial yellow phosphor and (b) the CsPbBr3 / PMMA-based WLED device in Example 2 to replace the white light source of a computer monitor. Figure 8 The dynamic light scattering (DLS) particle size distribution of the CsPbBr3 / PMMA composites obtained in Examples 1-4 shows that the size of the composite material increases with the increase of light exposure time. The particle size directly affects the various properties of the material, thereby allowing for the adjustment of the material's properties. Figure 9 A schematic diagram and printing results of electrofluid inkjet printing using CsPbBr3 / PMMA prepared in Example 2 as ink, and a photograph of the CsPbX3 sample obtained by anion exchange under a 365 nm ultraviolet lamp. Figure 9 The diagram above shows the printing results of electrohydraulic inkjet printing using CsPbBr3 / PMMA ink. Figure 9 From left to right, e represents the anion Cl. - ,Br - I - Photograph of CsPbX3 sample under 365 nm UV light; Figure 10 Images of samples prepared at photopolymerization times of 1 h, 2 h, 5 h and 8 h (Examples 1-4); Figure 11 The X-ray diffraction patterns (XRD) of the samples obtained in Examples 1, 3 and 4 are shown. Figure 12 This is a comparison diagram of the emission spectrum peak positions of the samples obtained in Examples 1, 3, and 4; Figure 13 The images show photographs and emission spectra of different halogen CsPbX3 / PMMA composite materials obtained by ion exchange using the composite luminescent material in Example 2. Detailed Implementation

[0017] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0018] Example 1 This embodiment provides a method for preparing a CsPbX3 perovskite quantum dot / polymer composite luminescent material, including the following steps: (1) CsBr (0.2 mmol), PbBr2 (0.4 mmol), oleylamine (2 mmol) and 2-bromopropionic acid (2 mmol) were mixed with 10 ml of N,N-dimethylformamide and stirred at room temperature for 30 min until completely dissolved to obtain a precursor solution. 0.7 ml of the precursor solution was injected into 10 ml of xylene solution under rapid stirring (700 r / min) and reacted at room temperature for 2 h to obtain a CsPbBr3 quantum dot solution emitting a bright green light; (2) Pour the CsPbBr3 quantum dot solution obtained in step (1) into a centrifuge tube, add the same volume of methyl acetate solution, centrifuge at 12000 r / min for 5 min, redissolve the precipitate after centrifugation with 4 ml xylene, and continue to centrifuge at 7000 r / min for 3 min to obtain a CsPbBr3 quantum dot colloidal solution with 2-bromopropionic acid as the ligand, and seal it in a 5 ml glass bottle; (3) Take 0.7 ml of the CsPbBr3 quantum dot colloidal solution from step (2) into a 5 ml glass bottle, and add xylene (0.5 ml), tetrahydrofuran (1.5 ml), and methyl methacrylate (0.5 ml) to the bottle. Then, purge the bottle with nitrogen for 5 min and seal the glass bottle. Photopolymerization reaction is carried out under stirring at 600 r / min and illumination at 12 W (365 nm UV lamp, 10 cm distance) for 1 h to obtain CsPbBr3 / PMMA composite luminescent material.

[0019] The particle size of the composite luminescent material is approximately 20 nm.

[0020] Example 2 This embodiment provides a method for preparing a CsPbX3 perovskite quantum dot / polymer composite luminescent material, including the following steps: (1) CsBr (0.2 mmol), PbBr2 (0.4 mmol), oleylamine (2 mmol) and 2-bromopropionic acid (2 mmol) were mixed with 10 ml of N,N-dimethylformamide and stirred at room temperature for 30 min until completely dissolved to obtain a precursor solution. 0.7 ml of the precursor solution was injected into 10 ml of xylene solution under rapid stirring (700 r / min) and reacted at room temperature for 2 h to obtain a CsPbBr3 quantum dot solution emitting a bright green light; (2) Pour the CsPbBr3 quantum dot solution obtained in step (1) into a centrifuge tube, add the same volume of methyl acetate solution, centrifuge at 12000 r / min for 5 min, redissolve the precipitate after centrifugation with 4 ml xylene, and continue to centrifuge at 7000 r / min for 3 min to obtain a CsPbBr3 quantum dot colloidal solution with 2-bromopropionic acid as the ligand, and seal it in a 5 ml glass bottle; (3) Take 0.7 ml of the CsPbBr3 quantum dot colloidal solution from step (2) into a 5 ml glass bottle, and add xylene (0.5 ml), tetrahydrofuran (1.5 ml), and methyl methacrylate (0.5 ml) to the bottle. Then, purge the bottle with nitrogen for 5 min and seal the glass bottle. The photopolymerization reaction is carried out under stirring at 600 r / min and illumination at 12 W (365 nm UV lamp, 10 cm distance) for 2 h to obtain CsPbBr3 / PMMA composite luminescent material.

[0021] in, Figure 2 The X-ray diffraction (XRD) pattern and Fourier transform infrared (FTIR) spectrum of CsPbBr3 quantum dots and CsPbBr3 / PMMA obtained in Example 2 are shown. Figure 2 (a) shows the X-ray diffraction patterns of CsPbBr3 quantum dots and CsPbBr3 / PMMA. The XRD images of both CsPbBr3 quantum dots and CsPbBr3 / PMMA match well with the standard card (PDF#54-0752) for cubic CsPbBr3, showing strong peaks at 15.2°, 21.2°, and 30.1°, corresponding to the (100), (110), and (200) crystal planes of cubic CsPbBr3, respectively. Furthermore, the CsPbBr3 / PMMA sample exhibits a broad peak at approximately 20° to 30°, which is caused by the amorphous PMMA polymer. The XRD results demonstrate that the photopolymerization process did not alter the crystal structure of the CsPbBr3 quantum dots, confirming the presence of both CsPbBr3 and PMMA phases in the composite material. Figure 2 (b) shows the FTIR spectra of CsPbBr3 quantum dots and CsPbBr3 / PMMA, with the 3440 cm⁻¹ value in the figure. -1The absorption peak at 2920 cm⁻¹ is due to the stretching vibration of the OH bond, originating from 2-BPA; -1 2985cm -1 1470 cm -1 1390 cm -1 and 840 cm -1 720 cm -1 The absorption peak at 1580 cm⁻¹ is caused by the bending vibration of the CH bond, originating from 2-BPA, OAm, and PMMA; -1 The absorption peak at approximately 700 cm⁻¹ is due to the bending vibration of the NH bond in OAm; -1 The absorption peak at 1650 cm⁻¹ is due to the vibration of the C-Br bond in 2-BPA; -1 and 1740 cm -1 The absorption peak at 1000 cm⁻¹ is due to the vibration of the C=O bonds on the carboxyl and ester groups; -1 The absorption peak at [location] is caused by the vibration of the C-C bond. The biggest difference between the FTIR spectra of CsPbBr3 quantum dots and CsPbBr3 / PMMA is at 1140 cm⁻¹. -1 and 1250 cm -1 The absorption peak originates from the COC bond stretching vibration of the ester group in the PMMA side group. These results demonstrate the presence of PMMA in the composite material and indicate that the characteristic bonds of the CsPbBr3 quantum dots before photopolymerization remain unchanged after photopolymerization.

[0022] Figure 3 Transmission electron microscope (TEM) images of CsPbBr3 quantum dots and CsPbBr3 / PMMA obtained in Example 2; Figure 3 Image a shows a TEM image of CsPbBr3 quantum dots prepared using 2-bromopropionic acid / oleylamine (2-BPA / OAm) as ligands. The obtained CsPbBr3 quantum dots are uniform in size, with an average size of approximately 8-10 nm. Figure 3 b is an HRTEM image of CsPbBr3 quantum dots. The quantum dots have good crystallinity, with a lattice fringe spacing of 0.42 nm, corresponding to the (110) crystal plane of cubic phase CsPbBr3. Figure 3 c is a TEM image of CsPbBr3 / PMMA. From the image, it can be seen that the composite material has a uniform particle size, and the TEM image contrast between the dark and bright areas is obvious. Figure 3 d), a bright shell uniformly coats the dark core, with individual particles approximately 13 nm in diameter and a shell thickness of approximately 2 nm. A lattice spacing of 0.28 nm can be clearly observed in the HRTEM image of the dark region in the middle of the composite material. Figure 3(d illustration) corresponds to the (200) crystal plane of the cubic phase CsPbBr3, indicating that the core is CsPbBr3 and the bright shell is PMMA. TEM images provide microscopic evidence of the formation of the core-shell CsPbBr3 / PMMA composite material.

[0023] Figure 4 The emission spectra and fluorescence decay curves of CsPbBr3 quantum dots and CsPbBr3 / PMMA obtained in Example 2 are shown. Figure 4 Figure a shows the absorption and emission spectra of CsPbBr3 quantum dots and CsPbBr3 / PMMA. The figure reveals that the emission peak positions are similar, with CsPbBr3 / PMMA (510 nm) showing a slight redshift compared to CsPbBr3 quantum dots (508 nm) (the absorption and emission spectra show consistent trends). This slight redshift is attributed to the quantum confinement effect caused by the size variation of the quantum dots. Furthermore, compared to CsPbBr3 quantum dots (FWHM = 19.7 nm), CsPbBr3 / PMMA has a narrower full width at half maximum (FWHM) of 18.7 nm. This is mainly because CsPbBr3 quantum dots in CsPbBr3 / PMMA are more easily dispersed in the solvent as single nanocrystals.

[45] In addition, CsPbBr3 / PMMA exhibits excellent luminescence properties, with a quantum efficiency of 85.7% ( Figure 3 c). Figure 4 b shows the fluorescence decay curves of CsPbBr3 quantum dots and CsPbBr3 / PMMA. By fitting the data with a double exponential function, it is shown that fluorescence decay occurs through two relaxation pathways. The first decay (τ1) is attributed to exciton radiative recombination, while the second (τ2) is related to trap-assisted exciton recombination on the perovskite quantum dot surface. Excitons trapped in shallow and / or deep defect states are released through a detrapping process, resulting in a longer decay lifetime. The decay lifetime of CsPbBr3 / PMMA is 16.18 ns, which is longer than that of CsPbBr3, indicating a reduction in nonradiative recombination. The longer decay lifetime is mainly due to the cross-linking of the generated long PMMA chains in the shell, which enhances the interaction between the ligand and the CsPbBr3 quantum dots. Furthermore, the presence of the long PMMA chains can effectively passivate defects on the CsPbBr3 quantum dot surface, giving CsPbBr3 / PMMA a longer fluorescence decay lifetime.

[0024] Figure 5 The curves showing the change in luminescence intensity of CsPbBr3 quantum dots and CsPbBr3 / PMMA obtained in Example 2 as a function of immersion time in water, and photographs of CsPbBr3 / PMMA samples immersed in water. Figure 5The images and functions showing the luminescence intensity changes of CsPbBr3 quantum dots and CsPbBr3 / PMMA with different immersion times in water are presented. The graphs show that the luminescence of CsPbBr3 quantum dots completely quenched after about 2 hours of immersion in water, while CsPbBr3 / PMMA maintained more than 75% of the initial luminescence intensity after 68 days of immersion, a significant improvement over CsPbBr3. This is mainly because the PMMA shell uniformly coats the surface of CsPbBr3, effectively isolating it from external moisture and better protecting CsPbBr3 in aquatic environments, thus expanding its application in high-humidity environments.

[0025] Figure 6 It is the CsPbBr3 / PMMA composite material obtained in Example 2 combined with a 460 nm blue light chip and K2SiF6:Mn 4+ Spectral images, emission photographs, and color gamut diagrams of white LED devices fabricated with red phosphors. Figure 6 a represents the CIE coordinates and color gamut of the white LED fabricated from the composite material. Figure 6 b represents the electroluminescence spectrum of the white LED device. Due to the good stability of CsPbBr3 / PMMA, it has potential applications in backlight displays. We combined the obtained CsPbBr3 / PMMA with the red phosphor K2SiF6:Mn 4+ WLED devices were fabricated using 460 nm blue LED chips. Figure 6 (Figure b). The luminous efficacy of the obtained device is 60.5 lm / W, and its CIE coordinates are (0.3109, 0.3170), as shown in Figure a, which is in the white light emission region. The color gamut of the obtained WLED device was compared with the NTSC 1931 standard, and its color gamut covers 129.5% of the NTSC 1931 standard.

[0026] Figure 7 For (a)Y3Al5O 12 A photograph of a display device obtained by soldering commercial yellow phosphor with the CsPbBr3 / PMMA-based WLED device from Example 2 (b) to replace the white light source of a computer monitor. (The image also shows the device with Y3Al5O3.) 12 Compared to the screens fabricated with CsPbBr3 / PMMA, the screens fabricated with Y3Al5O exhibit better display performance, especially in the green display area. 12 The base monitor exhibits a yellowish mixed color effect, while the CsPbBr3 / PMMA base monitor shows higher color saturation.

[0027] Example 3 This embodiment provides a method for preparing a CsPbX3 perovskite quantum dot / polymer composite luminescent material, including the following steps: (1) CsBr (0.2 mmol), PbBr2 (0.4 mmol), oleylamine (2 mmol) and 2-bromopropionic acid (2 mmol) were mixed with 10 ml of N,N-dimethylformamide and stirred at room temperature for 30 min until completely dissolved to obtain a precursor solution. 0.7 ml of the precursor solution was injected into 10 ml of xylene solution under rapid stirring (700 r / min) and reacted at room temperature for 2 h to obtain a CsPbBr3 quantum dot solution emitting a bright green light; (2) Pour the CsPbBr3 quantum dot solution obtained in step (1) into a centrifuge tube, add the same volume of methyl acetate solution, centrifuge at 12000 r / min for 5 min, redissolve the precipitate after centrifugation with 4 ml xylene, and continue to centrifuge at 7000 r / min for 3 min to obtain a CsPbBr3 quantum dot colloidal solution with 2-bromopropionic acid as the ligand, and seal it in a 5 ml glass bottle; (3) Take 0.7 ml of the CsPbBr3 quantum dot colloidal solution from step (2) into a 5 ml glass bottle, and add xylene (0.5 ml), tetrahydrofuran (1.5 ml), and methyl methacrylate (0.5 ml) to the bottle. Then, purge the bottle with nitrogen for 5 min and seal the glass bottle. The photopolymerization reaction is carried out under stirring at 600 r / min and illumination at 12 W (365 nm UV lamp, 10 cm distance) for 5 h to obtain the CsPbBr3 / PMMA composite luminescent material.

[0028] The particle size of the composite luminescent material is approximately 100 nm.

[0029] Example 4 This embodiment provides a method for preparing a CsPbX3 perovskite quantum dot / polymer composite luminescent material, including the following steps: (1) CsBr (0.2 mmol), PbBr2 (0.4 mmol), oleylamine (2 mmol) and 2-bromopropionic acid (2 mmol) were mixed with 10 ml of N,N-dimethylformamide and stirred at room temperature for 30 min until completely dissolved to obtain a precursor solution. 0.7 ml of the precursor solution was injected into 10 ml of xylene solution under rapid stirring (700 r / min) and reacted at room temperature for 2 h to obtain a CsPbBr3 quantum dot solution emitting a bright green light; (2) Pour the CsPbBr3 quantum dot solution obtained in step (1) into a centrifuge tube, add the same volume of methyl acetate solution, centrifuge at 12000 r / min for 5 min, redissolve the precipitate after centrifugation with 4 ml xylene, and continue to centrifuge at 7000 r / min for 3 min to obtain a CsPbBr3 quantum dot colloidal solution with 2-bromopropionic acid as the ligand, and seal it in a 5 ml glass bottle; (3) Take 0.7 ml of the CsPbBr3 quantum dot colloidal solution from step (2) into a 5 ml glass bottle, and add xylene (0.5 ml), tetrahydrofuran (1.5 ml), and methyl methacrylate (0.5 ml) to the bottle. Then, purge the bottle with nitrogen for 5 min and seal the glass bottle. The photopolymerization reaction is carried out under stirring at 600 r / min and illumination at 12 W (365 nm UV lamp, 10 cm distance) for 8 h to obtain the CsPbBr3 / PMMA composite luminescent material.

[0030] The particle size of the composite luminescent material is approximately 400 nm.

[0031] Figure 8 The image shows the dynamic light scattering (DLS) particle size distribution of the CsPbBr3 / PMMA composite materials obtained in Examples 1-4. The results indicate that the size of the composite material increases with the increase of light exposure time, and the particle size directly affects the various properties of the material, thereby allowing for the adjustment of the material's properties.

[0032] Figure 9 A schematic diagram and printing results of electrofluid inkjet printing using CsPbBr3 / PMMA prepared in Example 2 as ink, and a photograph of the CsPbX3 sample obtained by anion exchange under a 365 nm ultraviolet lamp. Figure 9 The diagram above shows the printing results of electrohydraulic inkjet printing using CsPbBr3 / PMMA ink. Figure 9 From left to right, e represents the anion Cl. - ,Br - I - A photograph of the CsPbX3 sample under a 365 nm UV lamp; this result demonstrates the broader application prospects of the composite material.

[0033] Figure 10 Images are of samples prepared at photopolymerization times of 1 h, 2 h, 5 h and 8 h (Examples 1-4). Figure 11 The X-ray diffraction (XRD) patterns of the samples obtained in Examples 1, 3 and 4 confirm that the illumination time used in each example can prepare CsPbBr3 / PMMA composite materials.

[0034] Figure 12 The figure shows a comparison of the emission spectrum peak positions of the samples obtained in Examples 1, 3 and 4. It can be seen from the figure that the photopolymerization time has no significant effect on the peak position of CsPbBr3 / PMMA, and all of them are located near 508 nm.

[0035] Figure 13 Photographs and emission spectra of different halogen CsPbX3 / PMMA composite materials obtained by ion exchange using the composite luminescent material in Example 2. Since halide ions directly participate in determining the band structure of the material, changing the halogen results in different band gaps for CsPbX3, thus leading to different wavelengths of absorbed and emitted light, exhibiting different colors. - →Br - →I - It exhibits a luminescent color that changes from blue-violet to green to red. This result indicates that Cl... - and I - The same applies to the method used in this invention, indicating that the method of this invention is universal for CsPbX3 (X = Cl, Br, I) perovskite quantum dots with different halogens.

[0036] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a CsPbX3 perovskite quantum dot / polymer composite luminescent material, characterized in that, Includes the following steps: (1) CsX, PbX2 are mixed with organic ligands and organic solvents and stirred until completely dissolved to obtain a precursor solution; the molar ratio of CsX, PbX2 and organic ligands is 1:2:20-1:2:40; the precursor solution is injected into a benzene solvent with a stirring speed of 400-700 r / min and reacted at room temperature to obtain a CsPbX3 quantum dot solution; wherein, X represents halogens Cl, Br, I; (2) Add the same volume of settling agent to the CsPbX3 quantum dot solution in step (1) and centrifuge to purify it, so as to obtain a CsPbX3 quantum dot colloidal solution; (3) The CsPbX3 quantum dot colloidal solution described in step (2) is subjected to photopolymerization reaction with the benzene solvent, tetrahydrofuran, and methyl methacrylate under a nitrogen atmosphere and under sealed stirring conditions to obtain the perovskite quantum dot / polymer composite luminescent material.

2. The preparation method of a CsPbX3 perovskite quantum dot / polymer composite luminescent material as described in claim 1, characterized in that, In step (1), the organic ligand is any one or a mixture of amine reagents, 2-halopropionic acid, 2-halobutyric acid or 2-haloisobutyric acid.

3. The preparation method of a CsPbX3 perovskite quantum dot / polymer composite luminescent material as described in claim 2, characterized in that, In steps (1)-(3), the benzene solvent is any one of toluene, xylene or ethylbenzene.

4. The preparation method of a CsPbX3 perovskite quantum dot / polymer composite luminescent material as described in claim 3, characterized in that, In step (2), the settling agent is one or more of ethyl acetate, methyl acetate, or acetone.

5. The preparation method of a CsPbX3 perovskite quantum dot / polymer composite luminescent material as described in claim 4, characterized in that, In step (2), the centrifugal purification process is as follows: centrifuge at 12000 r / min for 5-7 min, redissolve the precipitate after centrifugation with a benzene solvent, and continue centrifuging at 7000 r / min for 3-5 min.

6. The method for preparing a CsPbX3 perovskite quantum dot / polymer composite luminescent material as described in claim 5, characterized in that, In step (3), the volume ratio of benzene solvent, tetrahydrofuran and methyl methacrylate is 0.2-0.7:1.5-2.0:0.5-0.

7.

7. The method for preparing a CsPbX3 perovskite quantum dot / polymer composite luminescent material as described in claim 6, characterized in that, In step (3), the photopolymerization reaction conditions are: stirring speed of 500-700 r / min, ultraviolet light intensity of 12-25 W, distance of 10-20 cm, and photopolymerization time of 1-8 h.

8. A CsPbX3 perovskite quantum dot / polymer composite luminescent material prepared by the method according to any one of claims 1-7, characterized in that, The composite luminescent material is a core-shell structured nanomaterial obtained by in-situ growing a polymer shell on the surface of CsPbX3 quantum dots, with the core being CsPbX3 quantum dots embedded inside the polymer.

9. A CsPbX3 perovskite quantum dot / polymer composite luminescent material as described in claim 8, characterized in that, The excitation wavelength of the composite luminescent material is 250-500 nm, the emission wavelength is 400-700 nm, and the half-width at half maximum (WHM) of the emission spectrum is 12-42 nm; the particle size of the composite luminescent material is 10-400 nm.

10. The application of the CsPbX3 perovskite quantum dot / polymer composite luminescent material as described in claim 9, characterized in that, The perovskite composite luminescent material is used in Micro-LED devices and precision patterning.